"Crosstalk" technique: A comparison between two generations of cryoballoon catheter. Issue 6 (23rd April 2018) - Yang, Jian‐du; Sun, Qi; Guo, Xiao‐gang; Zhou, Gong‐bu; Liu, Xu; Luo, Bin; Wei, Hui‐qiang; Liang, Jackson J.; Ma, Jian
Abstract: Introduction: The "Crosstalk" technique: if pulmonary vein isolation (PVI) of the superior one is not achieved due to a gap in the inferior part, it could be done during inferior vein cryoablation. This maneuver minimizes the total energy delivery time and number of lesions. We aimed to correlate the likelihood of crosstalk phenomenon with certain anatomic characteristics. Methods: A total of 676 patients undergoing a first ablation procedure for paroxysmal or persistent atrial fibrillation (470 first‐generation cryoballoon [CB] and 206 second‐generation CB) between June 2014 and December 2016 were included. Results: "Crosstalk" phenomenon occurred in 32 patients (18 first‐generation CB, 14 second‐generation CB). Compared to 54 control patients without crosstalk, the angle between left superior pulmonary vein (LSPV) and left atrial (LA) roof‐plane, left pulmonary common ostia were significant parameters associated with crosstalk (odds ratio [OR] = 1.20, ±95% confidence interval [CI]: 1.11–1.31, P < 0.001; OR = 5.67, ±95% CI: 1.08–28.69, P = 0.04). As for angle between LSPV and LA roof‐plane, the cut‐off value was 28.68° with a sensitivity of 72.22%, a specificity of 81.25%, and an area under the receiver operating characteristic curve of 0.87 to predict the possibility of crosstalk technique application to get isolated in LSPV. Among the crosstalk group, there was no statistical difference between first‐generation CB and second‐generation CB in pulmonary anatomic characteristics. Conclusion: Crosstalk technique can be effective in patients with AF undergoing CB ablation using with both first and second‐generation CBs. Anatomic characteristics predictive of crosstalk include a left common ostia and smaller angle between the LSPV and LA roof‐plane.